Home victory for Brazil in the 2014 FIFA World Cup - Achim Zeileis; Christoph Leitner; Kurt Hornik (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
After 36 years the FIFA World Cup returns to South America with the 2014 event being hosted in Brazil (after 1978 in Argentina). And as in all previous South American FIFA World Cups, a South American team is expected to take the victory: Using a bookmaker consensus rating - obtained by aggregating winning odds from 22 online bookmakers - the clear favorite is the host Brazil with a forecasted winning probability of 22.5%, followed by three serious contenders. Neighbor country Argentina is the expected runner-up with a winning probability of 15.8% before Germany with 13.4% and Spain with 11.8%. All other competitors have much lower winning probabilities with the "best of the rest" being the "insider tip" Belgium with a predicted 4.8%. Furthermore, by complementing the bookmaker consensus results with simulations of the whole tournament, predicted pairwise probabilities for each possible game at the FIFA World Cup are obtained along with "survival" probabilities for each team proceeding to the different stages of the tournament. For example, it can be inferred that the most likely final is a match between neighbors Brazil and Argentina (6.5%) with the odds somewhat in favor of Brazil of winning such a final (with a winning probability of 57.8%). However, this outcome is by no means certain and many other courses of the tournament are not unlikely as will be presented here. All forecasts are the result of an aggregation of quoted winning odds for each team in the 2014 FIFA World Cup: These are first adjusted for profit margins ("overrounds"), averaged on the log-odds scale, and then transformed back to winning probabilities. Moreover, team abilities (or strengths) are approximated by an "inverse" procedure of tournament simulations, yielding estimates of probabilities for all possible pairwise matches at all stages of the tournament. This technique correctly predicted the EURO 2008 final (Leitner, Zeileis, and Hornik 2008), with better results than other rating/forecast methods (Leitner, Zeileis, and Hornik 2010a), and correctly predicted Spain as the 2010 FIFA World Champion (Leitner, Zeileis, and Hornik 2010b) and EURO 2012 Champion (Leitner, Zeileis, and Hornik 2012).
Keywords: C53; C40; D84; 330; consensus; agreement; bookmakers odds; tournament; 2014 FIFA World Cup